Cho x2+y2 = 2 (x,y thuộc R). CMR: xy(x-y)2 =< 1/2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
rút gọn P=2/x-(x2/(x2-xy)+(x2-y2)/xy-y2/(y2-xy)):(x2-xy+y2)/(x-y)
r tìm gt P với |2x-1|=1 ; |y+1|=1/2
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^2-\left(y+1\right)x+y^2-y=0\)
\(\Leftrightarrow x^2-\left(y+1\right)x+\dfrac{1}{4}\left(y+1\right)^2-\dfrac{1}{4}\left(y+1\right)^2+y^2-y=0\)
\(\Leftrightarrow\left(x-\dfrac{y+1}{2}\right)^2+\dfrac{3}{4}\left(y-1\right)^2-1=0\)
\(\Leftrightarrow\dfrac{3}{4}\left(y-1\right)^2-1=-\left(x-\dfrac{y+1}{2}\right)^2\le0\)
\(\Rightarrow\dfrac{3}{4}\left(y-1\right)^2\le1\)
\(\Rightarrow\left(y-1\right)^2\le\dfrac{4}{3}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1.
\(a,\left(-xy\right)\left(-2x^2y+3xy-7x\right)\)
\(=2x^3y^2-3x^2y^2+7x^2y\)
\(b,\left(\dfrac{1}{6}x^2y^2\right)\left(-0,3x^2y-0,4xy+1\right)\)
\(=-\dfrac{1}{20}x^4y^3-\dfrac{1}{15}x^3y^3+\dfrac{1}{6}x^2y^2\)
\(c,\left(x+y\right)\left(x^2+2xy+y^2\right)\)
\(=\left(x+y\right)^3\)
\(=x^3+3x^2y+3xy^2+y^3\)
\(d,\left(x-y\right)\left(x^2-2xy+y^2\right)\)
\(=\left(x-y\right)^3\)
\(=x^3-3x^2y+3xy^2-y^3\)
2.
\(a,\left(x-y\right)\left(x^2+xy+y^2\right)\)
\(=x^3-y^3\)
\(b,\left(x+y\right)\left(x^2-xy+y^2\right)\)
\(=x^3+y^3\)
\(c,\left(4x-1\right)\left(6y+1\right)-3x\left(8y+\dfrac{4}{3}\right)\)
\(=24xy+4x-6y-1-24xy-4x\)
\(=\left(24xy-24xy\right)+\left(4x-4x\right)-6y-1\)
\(=-6y-1\)
#Toru
![](https://rs.olm.vn/images/avt/0.png?1311)
1)
Ta có: x+y=2
nên \(\left(x+y\right)^2=4\)
\(\Leftrightarrow x^2+y^2+2xy=4\)
\(\Leftrightarrow2xy=2\)
hay xy=1
Ta có: \(x^3+y^3\)
\(=\left(x+y\right)^3-3xy\left(x+y\right)\)
\(=2^3-3\cdot1\cdot2\)
=2
2)\(x^2+y^2=\left(x+y\right)^2-2xy=8^2-2\cdot\left(-20\right)=104\)
\(x^3+y^3=\left(x+y\right)^3-3xy\left(x+y\right)=8^3-3\cdot\left(-20\right)\cdot8=512+480=992\)
\(x^2+y^2+xy=\left(x+y\right)^2-xy=8^2-\left(-20\right)=64+20=84\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^2+y^2+1\ge xy+x+y\)
\(\Leftrightarrow2x^2+2y^2+2\ge2xy+2x+2y\)
\(\Leftrightarrow2x^2+2y^2+2-2xy-2x-2y\ge0\)
\(\Leftrightarrow\left(x^2-2x+1\right)+\left(y^2-2y+1\right)+\left(x^2-2xy+y^2\right)\ge0\)
\(\Leftrightarrow\left(x-1\right)^2+\left(y-1\right)^2+\left(x-y\right)^2\ge0\left(đúng\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)